A new species and new records of millipedes of the family Diplomaragnidae (Diplopoda, Chordeumatida) from Altai - Mikhaljova, Elena V.; Nefediev, Pavel S.; Nefedieva, Julia S. (Zootaxa, 2008)
Altajosoma corniferum sp. n. is described from the Republic of Altai, Siberia, Russia. The new species differs from congeners mainly by the large, horn-shaped lateral sheath processes of the posterior gonopod colpocoxites. New faunistic records for Altai are given for other species of the family Diplomaragnidae. All currently known members of Diplomaragnidae from Altai are keyed, including the new species.